Associations of obesity and weight change with physical and mental impairments in elderly Chinese people. (February 2018) - Zhu, Jingjing; Xiang, Yong-Bing; Cai, Hui; Li, Honglan; Gao, Yu-Tang; Zheng, Wei; Shu, Xiao-Ou
Highlights: Obesity at or after middle age and weight gain during adulthood are associated with accelerated age-related functional impairments. Being underweight after age 70 is also associated with higher probabilities of functional decline. Abstract: Objective: To examine the associations between anthropometric measurements and functional impairments in a sample of urban elderly Chinese people. Methods: In two population-based cohort studies, the Shanghai Women's Health Study (SWHS) and Shanghai Men's Health Study (SMHS), 11, 505 men and 17, 166 women aged 70–88 years at the time of the functional assessment were studied. Weight history was collected and anthropometric data were taken at study enrollment (from 1996 to 2000 for the SWHS, 2002–2006 for the SMHS). Information on functional status and current weight was collected at the most recent follow-up survey (from 2011 to 2015). Logistic regression analyses were applied to estimate the associations of body mass index (BMI), waist-hip-ratio (WHR), and weight changes with functional decline. Results: After a median follow-up of 14.4 years (range 5.4–18.2 years), we found that BMI/WHR at or after middle age, and weight gain during adulthood were significantly associated with impaired walking ability and mental functioning. Being underweight after age 70 was associated with poorer hearing and/or vision as well as poorer memory. The associations between obesity and functional impairment were generally not modified by sex, comorbidity or exercise. Conclusion: Weight gain, obesity at or after middle age, and underweight after age 70 were associated with physical and mental functional impairments among elderly Chinese people. These findings highlight the importance of maintaining healthy weight to reduce age-related functional decline.